2020
DOI: 10.1038/s41598-020-72635-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gut microbiota in exclusively breast-fed and formula-fed babies: a study of 91 term infants

Abstract: To compare gut microbiota of healthy infants that were exclusively breast-fed or formula-fed, we recruited 91 infants, who were assigned into three different groups and fed by breast milk (30 babies), formula A (30 babies) or formula B (31 babies) exclusively for more than 4 months after birth. Faecal bacterial composition was tested. Among different groups, α diversity was lower in breast-fed group than formula-fed groups in 40 days of age, but increased significantly in 6 months of age. The Bifidobacterium r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
144
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(166 citation statements)
references
References 30 publications
(64 reference statements)
15
144
2
5
Order By: Relevance
“…Even though breast milk was initially considered sterile, microbial metabolites were detected in the colostrum, which is the first milk produced after birth [ 201 ]. Intestinal microbial composition analysis of exclusively breast-fed neonates has shown greater abundance of Bifidobacterium and Bacteroides genera, compared to formula-fed infants [ 201 , 221 , 222 , 223 , 224 ]. This finding has led to two possible conclusions: that there is probable bacterial trafficking via breast milk to the neonate and/or that breast milk is a better substrate for particular commensals than commercial infant formula [ 201 ].…”
Section: Early Nutrition-microbiota Crosstalk In Sensitive Time Wimentioning
confidence: 99%
“…Even though breast milk was initially considered sterile, microbial metabolites were detected in the colostrum, which is the first milk produced after birth [ 201 ]. Intestinal microbial composition analysis of exclusively breast-fed neonates has shown greater abundance of Bifidobacterium and Bacteroides genera, compared to formula-fed infants [ 201 , 221 , 222 , 223 , 224 ]. This finding has led to two possible conclusions: that there is probable bacterial trafficking via breast milk to the neonate and/or that breast milk is a better substrate for particular commensals than commercial infant formula [ 201 ].…”
Section: Early Nutrition-microbiota Crosstalk In Sensitive Time Wimentioning
confidence: 99%
“…On the contrary, formula-fed infants show a greater alpha-diversity in gastrointestinal bacterial colonies and decreased numbers of Bifidobacterium spp. and higher numbers of Veillonella and Clostridioides ( 26 , 31 , 33 , 34 ). A recent prospective observational study in preterm infants in a neonatal Intensive Care Unit, which attempted to reveal the effects of breastmilk in the gut microbiota, showed that preterm babies fed either with their mother’s own milk (MOM) or with pasteurized donor’s human milk (DHM) had closer microbiota profiles compared to the group of formula fed infants.…”
Section: Effects Of Breastfeeding On Neonates’ Bacterial Microbiotamentioning
confidence: 99%
“…Although many studies have explored the short and long-term influence of the mode of birth and the type of milk (breastmilk versus formula) on the infants' flora composition (33,(37)(38)(39)(40), fewer studies have addressed the second phase of nutrition, which could be defined as the time after the introduction of solid food and prior to weaning, and the third phase of nutrition that begins with weaning.…”
Section: Effects Of Introduction Of Infant Formulas and Solid Food Onmentioning
confidence: 99%
“…Compared to that in formula-fed infants, the intestinal microbiota of breastfed infants is richer in Lactobacilli and Bifidobacteria [ 58 ]. At the same time, a reduced number of Veillonellaceae , Enterococcaceae , Streptococcaceae and Lachnospiraceae is observed [ 79 ]. Many studies confirm the health-promoting effects of Lactobacillus bacteria derived from breast milk on the baby’s body.…”
Section: Bacteria Of the Genus Lactobacillus Spmentioning
confidence: 99%